Investigation of the Near Future Solar Energy Changes Using a Regional Climate Model over Istanbul, Türkiye - Duran, Yusuf; Yavuz, Elif; Ozkaya, Bestami; Yalcin, Yuksel; Varis, Cagatay; Kuzu, S. Levent (MDPI, 2024)
This study aims to assess potential changes in radiation values at the solar power plant facility in Istanbul using the RegCM. This analysis seeks to estimate the extent of the solar radiation changes and evaluate the production capacity of solar power in Istanbul in the future. The research involved installing an off-grid rooftop solar energy system. Meteorological parameters (temperature, etc.) and the system's outputs were monitored to evaluate the energy production and its relationship with these parameters. The performance of the Regional Climate Model version 5.0 (RegCMv5) in accurately representing surface solar radiation and temperature patterns was assessed by comparing it with measured monocrystalline solar panel output data. The impact of different cumulus convection schemes was examined on the sensitivity of the RegCM by analyzing surface solar radiation data over the initial three months. Long-term simulations were conducted with the representational concentration path (RCP) scenarios of 2.6, 4.5, and 8.5 spanning from 2023 to 2050 with convection schemes yielding the best results. All scenarios project a slight decrease in incoming surface radiation.
Keywords: photovoltaic power plant; insolation; cumulus convection schemes; RegCM; solar energy; PARAMETERIZATION; EUROPE; SCHEME; CLOUD; REPRESENTATION; CONVECTION; FLUXES; Energy & Fuels